Penerapan Teknik Peer Editing terhadap Ketuntasan Hasil Belajar Siswa Kelas X MA Mazroillah Lubuklinggau dalam Menyunting Teks Prosedur Kompleks - Nur Nisai Muslihah; Novita Nia (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2018)
The purpose of this study is to describe the Application of peer editing technique to the mastery of students learning achievement of Class X MA Mazroillah Lubuklinggau in Editing Text of Complex Procedure. This study uses quasiexperimental method with the research population of 49 students who are divided into two classes. The selected class as sample is X.II.S class. The data were collected with technical tests in the form of essay tests. The test results show that the average score of students is greater than the KKM or 78.87> 70 and the percentage of mastery reaches 89.29 percent. Based on the calculation results obtained to = 4.743. When consulted with t table with N-1 = 28-1 = 27 or db / df = 27) at significance level of 1percent is 2,771 and 5 percent significance level is 2.052. So to greater than tt either at the significance level of 1 percent or 5 percent, or 4,743> 2,771 and 4,743> 2,052. Thus the hypothesis in this study that the application of Peer Editing techniques can significantly complete the learning outcomes of Students Class X MA Mazroillah Lubuklinggau in editing the text of complex procedures proven truth Keywords: Peer Editing, Text Procedure Complex